1984
DOI: 10.1002/em.2860060310
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity screening of foods. II. Results with fruits and vegetables

Abstract: A survey of the mutagenic potential of a wide variety of food products has been initiated with results for 28 different beverages reported previously [Stoltz et al, 1982b]. Here, results for samples of 46 widely consumed fruits and vegetables from six general categories are given. Each sample was concentrated and fractionated by polarity and solubility to give five fractions, each of which was assayed for mutagenic potential with Salmonella typhimurium TA98 and TA100. Although statistical analysis of the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…31,62,63,[70][71][72][73][74][75][76] In vitro, mixed results were reported in the genotoxicity of vitis vinifera (grape)-derived ingredients, but in vivo, mostly negative results were obtained (Table 10). Fractions of raw grapes demonstrated potent mutagenic activity in an Ames test, 70 and water and ethanol extracts of red and white grapes enhanced mitomycin-C (MMC)-induced sister chromatid exchanges (SCEs) in an SCE assay in human lymphocytes, but there was no effect on SCEs without MMC. 31 Grape juice was also mutagenic in vitro, as demonstrated in the Ames test.…”
Section: Genotoxicitymentioning
confidence: 99%
“…31,62,63,[70][71][72][73][74][75][76] In vitro, mixed results were reported in the genotoxicity of vitis vinifera (grape)-derived ingredients, but in vivo, mostly negative results were obtained (Table 10). Fractions of raw grapes demonstrated potent mutagenic activity in an Ames test, 70 and water and ethanol extracts of red and white grapes enhanced mitomycin-C (MMC)-induced sister chromatid exchanges (SCEs) in an SCE assay in human lymphocytes, but there was no effect on SCEs without MMC. 31 Grape juice was also mutagenic in vitro, as demonstrated in the Ames test.…”
Section: Genotoxicitymentioning
confidence: 99%
“…The scientific reports assessing the genotoxic potential of phytocomplexes gave indeed controversial results in terms of safety and mutagenicity of grape-derived ingredients. In 1982 and 1984 Stoltz and colleagues [ 44 , 45 ] analyzed the mutagenic potential of a wide variety of food and food products by means of the Ames test. In their surveys, components of polar fractions of raw grapes and grape juice demonstrated potent mutagenic activity, both in the presence and absence of metabolic activation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of mutagenicity studies of Q-Actin, as evaluated by bacterial reverse mutation test (Ames assay), in vitro chromosomal aberration assay and in vivo micronucleus test in Swiss albino mice, did not reveal any genotoxic effects. In an earlier study, Stoltz et al [ 23 ] reported that an extract of cucumber in an Ames test using S. typhimurium TA98 and TA100 with and without metabolic activation was not mutagenic. The findings from the present study support these observations.…”
Section: Discussionmentioning
confidence: 99%